2005
DOI: 10.1093/ietisy/e88-d.9.2148
|View full text |Cite
|
Sign up to set email alerts
|

Java Birthmarks --Detecting the Software Theft--

Abstract: and Ken-ichi MATSUMOTO † , Members SUMMARY To detect the theft of Java class files efficiently, we propose a concept of Java birthmarks, which are unique and native characteristics of every class file. For a pair of class files p and q, if q has the same birthmark as p's, q is suspected as a copy of p. Ideally, the birthmarks should satisfy the following properties: (a) preservation -the birthmarks should be preserved even if the original class file is tampered with, and (b) distinction -independent class file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…Tamada birthmark [7] is the first practical application of static software birthmark for Java programs.  Inheritance Structure: Every Java program has class hierarchy beginning from java.lang.Object.…”
Section: Static Software Birthmarkmentioning
confidence: 99%
“…Tamada birthmark [7] is the first practical application of static software birthmark for Java programs.  Inheritance Structure: Every Java program has class hierarchy beginning from java.lang.Object.…”
Section: Static Software Birthmarkmentioning
confidence: 99%
“…Tamada et al [2], [3] first suggested a practical application of static software birthmarks and presented a method to compare the birthmarks for Java class files. Their technique consists of four individual birthmarks: constant values in field variables, sequence of method calls, inheritance structure, and used classes.…”
Section: Related Workmentioning
confidence: 99%
“…To measure discrimination capability, the threshold value for determining code clones was set as = 0.2, which was determined to maximize precision and recall in the detection of common modules in Java programs [12]. To evaluate and compare performance of the proposed method, Stigmata 2.0 † was used for the Tamada birthmark [2], [3] and the kgram birthmark [4], [5]. We also compared the performance of the stack pattern birthmark [6].…”
Section: Discrimination Between Independent Programsmentioning
confidence: 99%
See 2 more Smart Citations